Aesthetic injustice. Issue 1 (1st January 2020) - Dalaqua, Gustavo H.
ABSTRACT: In this article, the author advances the concept of aesthetic injustice, which denotes any harm done to someone specifically in her capacity as an aesthetic being, and explores four dimensions of this new philosophical concept. First, the author appeals to the notion of colonial mentality presented by Amílcar Cabral in order to show how aesthetic injustice is experienced differently by the oppressors and the oppressed. Then, the author engages critically with Augusto Boal's The Aesthetics of the Oppressed and underscores the mutual influence between aesthetic injustice and epistemic injustice. Next, the author suggests how both types of injustice may be resisted by dint of an analysis of Boal's Theatre of the Oppressed and The Rainbow of Desire . The author concludes by examining how aesthetic injustice is inimical to democracy and by explaining why a democratic regime requires aesthetic justice, a normative concept according to which all citizens are equally entitled to have their way of seeing and feeling about public issues taken into account in political deliberation.